(untitled) (Biological Sciences - PJSIR, 2008)
. The mechanism of salt tolerance in relation to individual leaf growth, transpiration, dark respiration rate, and quantum yield was studied at 0, 50 and 100 mM NaCl solution. At high salt concentration the leaves of BM21 showed higher reduction in growth than those of BM 01. The relative reduction (% of control) of Tr and Dr were less in BM01 than in BM21. The dark respiration rates were less than 1 mmol (CO )/m2/s and accounted for 19 and 32% increase (% of control) at the highest PFD in BM01, while it was 31 and 44% in BM21, respectively at 50 and 100 mM NaCl. More reduced quantum yield in BM21 than BM01 reflects more maintenance costs of energy in repairing injured tissue, enzyme reactions and ion movement.